A short linear motif in scaffold Nup145C connects Y-complex with pre-assembled outer ring Nup82 complex - Teimer, Roman; Kosinski, Jan; Appen, Alexander von; Beck, Martin; Hurt, Ed (Nature Communications, 2017)
The Nup82-Nup159-Nsp1 complex, which plays a key role in mRNA export, is recruited late during the process of nuclear pore complex (NPC) assembly. Here the authors combine crosslinking mass spectrometry, biochemical reconstitution and molecular modeling to gain insights into the mechanism of Nup82 recruitment to the NPC.